(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new record in Italy of the mealybug Phenacoccus solani Ferris (Homoptera Coccoidea) on Encephalartos sp. (Cycadaceae) in cold greenhouse is reported together with some morphological comments.